MODERN LIFE-CYCLE RITUALS OF THE RUSSIANS OF THE KIZLYAR REGION: TRADITION AND INNOVATION - Seferbekov, Ruslan Ibragimovic (History, Archeology and Ethnography of the Caucasus, 2025)
The article explores the traditional and contemporary life-cycle rites of ethnic Russians in the Kizlyar region of Dagestan. It employs general scientific and specialized historical and ethnological methods, supplemented by ethnographic fieldwork conducted in villages across the Kizlyar and Tarumovsky districts. These rites were significantly reshaped by globalization and the sociocultural shifts that occurred between the second half of the 1980s and the first quarter of the 21st century. Initially, some of these processes detrimentally affected the economic activities and family life of ethnic Russians in Dagestan, resulting in a decline in their overall standard of living. However, the subsequent economic stabilization of the 2000s positively impacted both their economic and family spheres. This stabilization particularly fostered the widespread expansion of the wedding industry, which, in turn, led to a shortening of the duration and stages of the wedding ceremony and the loss of some traditional elements. Furthermore, Christianity has exerted a profound influence on these life-cycle rites, an influence evident across all their constituent elements. The influence of globalization is evident in several contemporary practices, such as the use of digital devices and social media for young men and women to meet, the increasingly common organization of professional photo sessions during the wedding procession, and the growing popularity of the “Tooth Fairy” ritual associated with the loss of a child’s first tooth. Despite these global influences, traditional Slavic rituals remain integral to the family and everyday life-cycle rites of Russians in the Kizlyar region. These traditions are evident in the structured stages and specific content of the wedding ceremony, the composition of its participants, and in measures dedicated to preserving the life and health of both mother and child. Furthermore, a significant layer of beliefs and customs, including remnants of oneiromancy (divination by dreams) and ancestor worship, persists. A study of the life-cycle rituals among Dagestan’s rural Russian population thus reveals the successful preservation of a substantial portion of their traditional culture. This enduring heritage plays a crucial role in maintaining their ethnic, national, cultural, and religious identity in the face of widespread globalization.